"The business is about knowing who to sell to": Nigerian retail-level drug dealers' strategies for avoiding police arrest. (March 2022) - Nelson, Ediomo-Ubong E.; Ramirez, Tasha M.
Abstract: Drawing on semi-structured interviews with 31 male commercially-oriented retail dealers selling multiple substances in a street-level drug market recruited through snowball sampling in Uyo, Nigeria, this study explores situated strategies for minimizing the risk of police arrest. Findings highlight four broad strategies: selling to genuine buyers, using mobile phones, discreet transactions, and temporary desistance. These strategies are situated within local drug markets and law enforcement context. Strategies were oriented towards avoiding arrest for criminal complicity, negotiating changing relationship to law enforcement, and reducing visibility through a combination of phone calls and delivery services. It is argued that while restrictive deterrence may displace retail drug dealing, it does not lead to overall reduction in frequency of sales. Further, police complicity in drug trade through bribery limits restrictive deterrence. Measures that prioritize the demand-side of drug markets, including treatment for dependent users, should be considered, while refocusing law enforcement on large-scale traffickers.